An exploratory study on the impact of mobile ICT on productivity in construction projects. Issue 3 (9th July 2018) - Hasan, Abid; Elmualim, Abbas; Rameezdeen, Raufdeen; Baroudi, Bassam; Marshall, Andrew
Abstract : Purpose: The issue of low productivity has remained a very stern and chronic problem in construction projects. Previous studies have found poor communication as one of the leading causes of low-construction productivity. Recent advances in the field of information and communication technologies (ICT) have the potential to enhance communication and access to information in construction projects. However, the implications of the use of mobile ICT on construction productivity have not been investigated in sufficient depth, especially from the perspectives of its users, i.e. construction management (CM) professionals. The paper aims to discuss these issues. Design/methodology/approach: A focus group session involving ten experienced CM professionals from different organisations of the South Australian construction industry was moderated by a group of four researchers to gather data on mobile ICT usage and its implications for construction productivity. Findings: Lack of training and guidelines on effective applications of these technologies to construction projects is a major bottleneck. Results indicate that despite noticeable advances in mobile ICT, differences in usage style and user attitude have limited their overall impact on productivity. Research limitations/implications: This paper is based on data gathered from CM professionals working in the South Australian construction industry. Practical implications: The study highlights the importance of strategising the use of mobile ICT to achieve the desired productivity rates through policy, training, work-life balance, and deeper and wider understanding of these technologies. Originality/value: The study examines the perceptions of CM professionals on the usefulness of mobile ICT in construction projects and its implications for construction productivity.